Metastatic infection during Staphylococcus aureus bacteremia. Issue 2 (February 2020) - Horino, Tetsuya; Hori, Seiji
Abstract: Staphylococcus aureus causes various infections, including skin and soft tissue infections and pneumonia via both, community-associated and nosocomial infection. These infectious diseases can lead to bacteremia, and may subsequently result in metastatic infections in several cases. Metastatic infections are critical complications in patients with S. aureus bacteremia, since the optimal duration of the antimicrobial treatment differs in patients with and without metastatic infection. Notably, two weeks of antimicrobial treatment is recommended in case of uncomplicated S. aureus bacteremia, whereas in patients with S. aureus bacteremia-associated endocarditis or vertebral osteomyelitis, six weeks of antimicrobial administration is vital. In addition, misdiagnosis or insufficient treatment in metastatic infection is associated with poor prognosis, functional disability, and relapse. Although echocardiography is recommended to examine endocarditis in the patients with S. aureus bacteremia, it remains unclear which patients should undergo additional examinations, such as CT and MRI, to detect the presence of other metastatic infections. Clinical studies have revealed that permanent foreign body and persistent bacteremia are predictive factors for metastatic infections, and experimental studies have demonstrated that the virulence factors of S. aureus, such as fnbA and clfA, are associated with endocarditis; however, these factors are not proven to increase the risk of metastatic infections. In this review, we assessed the incidence, predictive factors, diagnosis, and treatment for metastatic infections during S. aureus bacteremia.